2023
DOI: 10.4490/algae.2023.38.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic diversity and phylogeographic patterns of <italic>Plocamium telfairiae</italic> and <italic>P. cartilagineum</italic> (Plocamiales, Rhodophyta) in the Northwest Pacific

Mi Yeon Yang,
Myung Sook Kim

Abstract: Cryptic diversity refers to two or more distinct species classified as a single species due to lack of morphological difference. Although Plocamium Lamouroux has potential applications in biotechnology, several phylogenetic studies suggest the presence of cryptic diversity within the genus that requires further phylogenetic evaluation. Here, we investigated two species of Plocamium, P. “cartilagineum” and P. “telfairiae”, in the Northwest (NW) Pacific. The aims of this study are to identify potential cryptic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(85 reference statements)
0
0
0
Order By: Relevance
“…The majority haplotype, MK01, was the common ancestor and the most widespread haplotype because of its prevalence in all the localities analyzed. We found that COI-5P sequences from M. pilulaora showed relatively lower haplotype diversity (Hd = 0.547) than COI-5P sequences from other red macroalgae in the northwest Pacific (Hd = 0.809 in Plocamium luculentum [Yang and Kim 2023]; Hd = 0.665 in Gracilaria vermiculophylla [Zhong et al 2020]; Hd = 0.626 in Chondrus ocellatus [Yang and Kim 2022]; Hd = 0.530 in Chondrus nipponicus [Yang and Kim 2022]). Interestingly, the pattern of the haplotype network of M. pilulaora was similar to that of other red macroalgae in Korea, which showed one or two prevailing haplotypes distributed widely, and several haplotypes derived from the prevailing haplotypes (Yang et al 2021a, b;Yang and Kim 2022).…”
Section: Discussionmentioning
confidence: 77%
“…The majority haplotype, MK01, was the common ancestor and the most widespread haplotype because of its prevalence in all the localities analyzed. We found that COI-5P sequences from M. pilulaora showed relatively lower haplotype diversity (Hd = 0.547) than COI-5P sequences from other red macroalgae in the northwest Pacific (Hd = 0.809 in Plocamium luculentum [Yang and Kim 2023]; Hd = 0.665 in Gracilaria vermiculophylla [Zhong et al 2020]; Hd = 0.626 in Chondrus ocellatus [Yang and Kim 2022]; Hd = 0.530 in Chondrus nipponicus [Yang and Kim 2022]). Interestingly, the pattern of the haplotype network of M. pilulaora was similar to that of other red macroalgae in Korea, which showed one or two prevailing haplotypes distributed widely, and several haplotypes derived from the prevailing haplotypes (Yang et al 2021a, b;Yang and Kim 2022).…”
Section: Discussionmentioning
confidence: 77%